DESIGN SPREAD SPECTRUM COMMUNICATION SYSTEM SIMULATION (Software) - Andy Soeseno; Yoedy Moegiharto; Arna Fariza (KH. A. Wahab Hasbullah University, 2008)
In this paper was design direct sequence spread spectrum simulation program consist of include the program of pseudo noise code generator by using gold codes method, spreading and despreading program. The sequence of pseudo noise code generated in 7 chips for 5 bits binary data information and 15 chips for 4 bit binary data information. The program of spreading simulation can provides sequence of spread spectrum signal and the program of despreading can recovery the original information signal. Keyword : spreading , desprading, pseudo noise code, chip, gold codes.